The dissociation of semantically congruent and incongruent cross-modal effects on the visual attentional blink - Zhao, Song; Zhou, Yuxin; Ma, Fangfang; Xie, Jimei; Feng, Chengzhi; Feng, Wenfeng (Frontiers in Neuroscience, 2023)
Recent studies have found that the sound-induced alleviation of visual attentional blink, a well-known phenomenon exemplifying the beneficial influence of multisensory integration on time-based attention, was larger when that sound was semantically congruent relative to incongruent with the second visual target (T2). Although such an audiovisual congruency effect has been attributed mainly to the semantic conflict carried by the incongruent sound restraining that sound from facilitating T2 processing, it is still unclear whether the integrated semantic information carried by the congruent sound benefits T2 processing. To dissociate the congruence-induced benefit and incongruence-induced reduction in the alleviation of visual attentional blink at the behavioral and neural levels, the present study combined behavioral measures and event-related potential (ERP) recordings in a visual attentional blink task wherein the T2-accompanying sound, when delivered, could be semantically neutral in addition to congruent or incongruent with respect to T2. The behavioral data clearly showed that compared to the neutral sound, the congruent sound improved T2 discrimination during the blink to a higher degree while the incongruent sound improved it to a lesser degree. The T2-locked ERP data revealed that the early occipital cross-modal N195 component (192-228 ms after T2 onset) was uniquely larger in the congruent-sound condition than in the neutral-sound and incongruent-sound conditions, whereas the late parietal cross-modal N440 component (400-500 ms) was prominent only in the incongruent-sound condition. These findings provide strong evidence that the modulating effect of audiovisual semantic congruency on the sound-induced alleviation of visual attentional blink contains not only a late incongruence-induced cost but also an early congruence-induced benefit, thereby demonstrating for the first time an unequivocal congruent-sound-induced benefit in alleviating the limitation of time-based visual attention.